Bidirectional Luo Converter Fed Switched Reluctance Motor - R. Balamurugan; M. Vishvanath (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The present work aims at designing and modelling of a bidirectional DC-DC LUO converter for driving a Switched Reluctance Motor. LUO converters are new series of DC/DC Converters that have very low ripple of voltage and current and have output wave with high quality, high power density and high transfer voltage gain and don’t have circuit elements parasitic limits of traditional converters. LUO converters have very high voltage transfer gains in geometric progression on stage by-stage. A C- Dump converter is used to drive the SRM drive. The present design aims at improving the efficiency of the Switched Reluctance Motor drive system by the incorporation of the bidirectional DC-DC LUO converter between the electrical source and the drive system.  http://dx.doi.org/10.11591/telkomnika.v12i12.6883